Μελέτη τοποθέτησης υπηρεσιών σε δικτυοκεντρικά περιβάλλοντα με Αλγεβρική Θεωρία Γράφων - (:unkn) unknown (My University, 2019)
Στα σημερινά δίκτυα ένα σημαντικό πρόβλημα που συναντάμε είναι η τοποθέτηση υπηρεσιών λόγο του αυξημένου αριθμού των κόμβων που υπάρχουν στα δίκτυα. Στόχος είναι να ελαχιστοποιήθει το κόστος μέσα στο δίκτυο δηλαδή που θα τοποθετηθεί η υπηρεσία ώστε όλοι οι κόμβοι να έχουν το ελάχιστο κόστος από αυτόν. To πρόβλημα αυτού του τύπου είναι αντικείμενο μελέτης του Fasility Location και πιο συγκεκριμένα το πρόβλημα αυτό ονομάζεται 1-median. Υπάρχουν αρκετές λύσεις και καλές προσεγγίσεις για την τοποθέτηση της υπηρεσίας στο δίκτυο ειδικότερα θα χρησιμοποιήσουμε την αλγεβρική θεωρία γράφων για την τοποθέτηση της υπηρεσίας στο δίκτυο. Η βέλτιστη λύσει δίνεται από το Clossenes Centrality, το Degree και Eigenvector Centality δεν δίνουν πάντα την βέλτιστη λύση άλλα μια προσέγγιση για το που θα τοποθετηθεί η υπηρεσία. Το en Clossenes Centrality για μεγάλα δίκτυα έχει τεράστιο κόστος υπολογισμού , στόχος της πτυχιακής είναι να εξετάσουμε πόσο καλή είναι οι προσεγγίσεις των μέτρων σε σχέση με το Clossenes Centrality

Ιn the 21st century we are in the Ιnformation Αge. An important role in shaping it has been computer networks. Changing the way we share information and services. In our everyday life we enjoy and use several services. An important problem that we encounter is the Fasility Location and more specifically the case of 1-median. The 1-median problem is a special category of the p-median problem. The problem is NP-hard on general graphs and networks for an arbitrary p (where p is a variable). Polynomial time algorithms exist for arbitrary p when the network is a tree. The aim of the thesis is to study where to place the service on the network and how close we are to the optimal solution using Algebraic Graph Theory. The optimal solution for the 1-median is given by Closeness centrality however there are other centrality measures such as Degree and Εigenvector centrality which provide approaches for optimal solution. For the comparison of the measures, we constructed networks consisting of geometric random with 1000 nodes. For the evaluation of the measures we have defined the concept of total cost for the network and and compared the computation time of each measure. Τhe results of Εigenvector centrality with use of Power Method is interesting because it has a very good approach to the placement of the service with a small computation time.
Keywords: Αλγεβρική Θεωρία Γράφων, Ιδιοτιµές , Ιδιοδιανύσµατα,Γραμμική Άλγεβρα, Θεωρία Γραφημάτων, Πίνακας γειτνίασης, Δίκτυα , Τοποθέτηση υπηρεσιών; 1-median, Closeness centrality , Degree centrality , Eigenvector centrality, power method, Eigenvectors , eigenvalues, Adjacency matrix, Linear Algebra, shortest path tree, shortest path, Facility location problem